Unfolding the Dynamics of Mineral Nutrients and Major Storage Protein Fractions during Soybean Seed Development - Montanha, Gabriel Sgarbiero; Carvalho Mendes, Nandhara Angélica [UNESP]; Perez, Lucas Coan; Oliveira Cunha, Matheus Luís [UNESP]; Santos, Eduardo; Pérez, Carlos Alberto; de Almeida, Eduardo; Marques, João Paulo Rodrigues; Umburanas, Renan Caldas; Linhares, Francisco Scaglia; dos Reis, André Rodrigues [UNESP]; Sabatini, Sabrina; et al. (American Chemical Society (ACS), 2023)
This study explored a field-based approach to precisely characterize the dynamics of the storage proteins (albumins and globulins fractions) biosynthesis and mineral nutrient accumulation (phosphorus, potassium, calcium, magnesium, sulfur, iron, boron, manganese, zinc, and copper) profile throughout the development of soybean seeds. Storage protein biosynthesis does not follow a linear progression from the beginning of seed filling (R5.1) until the full maturity (R8) stage, whereas it is accompanied by sulfur and magnesium demand peaks. Globulin concentration was consistently higher than the albumins at all developmental stages and reached an accumulation peak in the R6 stage. These results depict an intricate association between sulfur and magnesium concentration and the biosynthesis of storage proteins in soybean seeds.
Keywords: albumins; elemental composition; elemental distribution; globulins; Glycine max; soybean seeds; storage proteins